Liberação de linhagens de Trichogramma pretiosum para controle biológico de Spodoptera frugiperda na cultura do milho - Cordeiro, Ederval Silva (2006)
The objectives of this work were: to identify lineages of Trichogramma which occur naturally in eggs of Spodoptera frugiperda, in the West of Paran?; to select, under laboratory conditions, about eggs of the alternative host Anagasta kuehniella (Zeller), the lineage with the highest potential of parasitism and to evaluate the efficency of the selected line to control S. frugiperda in field conditions. Collections were realized in commercial, conventional and organic crops in properties in the West of Paran?. The collected lineages in the field were named (E1, E3, L3) and after, identified as T. pretiosum. The biology of the collected lineages in the field and the line (L2) breeded massively under laboratory conditions in Anagasta kuehniella eggs, were realized in temperature of 25?2 ?C; 70 ? 10% R.U. and 14 h. photophase. After the line selection through the analysis of biological parameters, two liberation experiments were performed in field conditions. On experiment 1, 100 thousand parasitoids per hectare were liberated and evaluated weekly, evaluating the plants which sufferd or not, the fall armyworm attack, observing the leaf damages, as scrape and perforation. On experiment 2, 200 thousand parasitoids per hectare were liberated and evaluated weekly, observing the same damages caused by Spodoptera related on the previous experiment. L2 was selected, due to this line large number of parasited eggs and larger number of females presented, when compared to males for later use in the field. In general, the conclusion is that in both experiments (1 and 2), there was significant reduction of the number of the damaged plants by S. frugiperda in treated areas with T. pretiosum